Investigations of p-type signal for ZnO thin films grown on (100) GaAs substrates by pulsed laser deposition - Rogers, D.J.
In this work we investigated ZnO films grown on semi-insulating (100) GaAs substrates by pulsed laser deposition. Samples were studied using techniques including X-ray diffraction (XRD), scanning electron microscopy, atomic force microscopy, Raman spectroscopy, temperature dependent photoluminescence, C-V profiling and temperature dependent Hall measurements. The Hall measurements showed a clear p-type response with a relatively high mobility (∼260 cm 2/Vs) and a carrier concentration of ∼1.8 × 1019 cm-3. C-V profiling confirmed a p-type response. XRD and Raman spectroscopy indicated the presence of (0002) oriented wurtzite ZnO plus secondary phase(s) including (101) oriented Zn2As2O 7. The results suggest that significant atomic mixing was occurring at the film/substrate interface for films grown at substrate temperatures of 450°C (without post-annealing).